Long non-coding RNA NEAT1 functions as a competing endogenous RNA to regulate S100A9 expression by sponging miR-196a-5p in rosacea. Issue 1 (April 2021) - Wang, Lian; Wang, Yu-Jia; Hao, Dan; Wang, Xiao-Yun; Li, Xiao-Xue; Zhao, Qian; Li, Yan-Mei; He, Gu; Jiang, Xian
Highlights: The study is the first genome-wide lncRNA profiling of paired lesioned and non-lesioned samples from rosacea patients. NEAT1 may functioned as a ceRNA mechanism by sponging miR-196a-5p/S100A9 to regulate inflammatory responses in rosacea. NEAT1/miR-196a-5p/S100A9 may be a novel target for the treatment of rosacea. Abstract: Background: Rosacea is a complex, chronic, and recurrent dermatologic condition that adversely affects quality of life and self-esteem. However, clinical relevance and molecular mechanisms underlying NEAT1 influence in rosacea remain unclear. Objective: The present study aims to investigate the dynamics and influences of lncRNAs, miRNAs, and mRNAs in rosacea patients, and to explore the impacts of NEAT1 treatments on miR-196a-5p and S100A9 expression in LL37-treated HaCaT cells. Methods: RNA-sequencing of skin tissues from rosacea patients and integrative analyses facilitated comprehensive exploration of lncRNA, mRNA, and miRNA networks. We identified differentially expressed lncRNAs in paired rosacea afflicted and non-lesioned tissues by hub lncRNAs in the ceRNA network. The role of NEAT1 in LL37-treated HaCaT cells was identified by in vitro experiments. Results: There were 237 lncRNAs, 38 miRNAs, and 1784 mRNAs in lesioned skin compared to non-lesioned skin in six rosacea patients. NEAT1 was upregulated in rosacea skin and in LL37-treated HaCaT cells. Moreover, inflammatory damage was able to be reduced in vitro after knockdown of NEAT1. Finally, NEAT1 was able to directly interact with miR‐196a-5p, and downregulating miR‐196a-5p was efficient in reversing the influence of NEAT1 siRNA on S100A9. Conclusion: We have completed the first genome-wide lncRNA profiling of paired lesioned and non-lesioned samples from rosacea afflicted patients. The NEAT1/miR-196a-5p/S100A9 axis may have played an important role in the dynamics underlying inflammatory responses of rosacea. NEAT1 may have functioned as a competing endogenous RNA which regulated inflammatory responses in rosacea by sponging miR-196a-5p and upregulating S100A9 expression.